Seaweed-based dripping stimulates root growth of dragon fruit (Hylocereus undatus [Haw.] Britton & Rose) stem cuttings - Potente, Mayalene M.; Manigo, Bryl I. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Developing a solid root system is essential in dragon fruit propagation not only for securing the succulent stem but also for facilitating the absorption of water and essential minerals from the soil. However, dragon fruit stem cuttings normally develop good root system for about 4-6 months after planting. There are commercially available growth hormones which hasten rooting, but these are relatively expensive. Hence, alternative hormones from natural materials that possess the ability to stimulate rooting are extensively explored. The efficacy of seaweed-based drippings (SD) as potential rooting bio-stimulant for dragon fruit cuttings were evaluated under nursery condition. Branch cuttings (30 cm long) were soaked at 6, 12 and 18 h at the rate of 50 mL, 100 mL and 150 mL SD per liter of water (H2O), with H2O, and ANAA (5 mL/L of H2O) served as positive and negative control treatments, respectively. There were 18 cuttings in each experimental units, replicated thrice and arranged in a 3 × 5 Completely Randomized Design (CRD). Results showed that 12 h soaking initiated more and longer roots and shoots. In addition, it appeared that the application of a solution containing SD at 100 mL/L of H20 resulted in the development of numerous and longer roots and shoots, a larger number of lateral roots, and a greater root-shoot ratio than other treatments. Furthermore, application of SD at 100 mL/L of H20 through dipping for 12 h developed more lateral roots compared to other treatment combinations. In conclusion, it can be inferred that the presence of phytohormones, such as auxins, in seaweed concentrates has the potential to effectively stimulate root formation in pitaya.